Direct jet impingement cooling of power electronics - Skuriat, Robert (2012)
The aim of the work presented in this thesis is to improve the operational reliability of a power module and increase the efficiency of its associated cooling system by integrating the design of the cooler as part of the module. Power modules are increasingly used in a variety of applications ranging from aircraft and mass transport systems, to motor control and power conversion in the home. Reliability of the power module is very important in aerospace applications where the highest levels of safety and robustness are required while keeping the volume and mass of the module as low as possible. Certain parts of the power module such as the solder layer beneath the silicon device and the substrate are prone to failure with thermal cycling. The layer of thermal grease between the baseplate of the module and the heatsink significantly increases the thermal resistance between the electronic devices and the coolant fluid. The power module can be constructed so that some of the interfaces within the module which are prone to failure are improved or completely removed from the assembly greatly reducing the thermal resistance from junction to ambient. The research identified cooling methods which are able to cope with the increasingly high heat fluxes produced by power electronic devices. Jet impingement cooling was selected for testing and further development. An initial series of tests confirmed that liquid jet impingement can be used to generate high heat transfer coefficients for the efficient cooling of power modules. Results from experimental tests showed that directly cooling the substrate tile with jet impingement resulted in the devices being cooled more effectively compared to the commonly used serpentine coldplate and a direct-baseplate cooled jet impingement system. It was postulated that more efficient cooling can be achieved by targeting the hotspots on the substrate beneath each device with a carefully designed impingement array. A test apparatus was constructed to test a variety of jet impingement arrays to confirm the hypothesis. A second test apparatus was constructed to characterise the performance of the jet arrays in more detail using a thermal imaging camera to monitor the surface temperature of a single device. An optimal jet configuration was found for the efficient cooling of a single device. The work concluded that an improvement in efficiency and reliability can be gained by constructing power modules with integrated jet impingement arrays direct-substrate cooling the hotspots beneath the devices.